Assessment of contribution of BCRP to intestinal absorption of various drugs using portal‐systemic blood concentration difference model in mice - Iichiro Kawahara; Satoyo Nishikawa; Akira Yamamoto; Yusuke Kono; Takuya Fujita (Wiley, 2020)
Abstract Prediction of the intestinal absorption of new chemical entities (NCEs) is still difficult, in part because drug efflux transporters, including breast cancer resistance protein (BCRP) and P‐glycoprotein (P‐gp), restrict their intestinal permeability. We have demonstrated that the absorptive quotient (AQ) obtained from the in vitro Caco‐2 permeability study would be a valuable parameter for estimating the impact of BCRP on the intestinal absorption of drugs. In this study, in order to assess the correlation between the in vitro AQ for BCRP and in vivo contribution of BCRP on drug absorption, we evaluated the oral absorption of various compounds by portal‐systemic blood concentration (P‐S) difference method in wild‐type (WT), Bcrp(−/−), and Mdr1a/1b(−/−) mice. In addition, we also calculated a rate of BCRP contribution (Rbcrp). Ciprofloxacin and nitrofurantoin showed the low Rbcrp value (0.05 and 0.15), and their apparent fractions of intestinal absorption in WT mice were 46.5% and 63.7%, respectively. These results suggest that BCRP hardly affects their intestinal absorption in mice. On the other hand, the apparent fraction of intestinal absorption of topotecan and sulfasalazine was significantly lower in WT mice than in Bcrp(−/−) mice. Moreover, their Rbcrp values were 0.42 and 0.79, respectively, indicating the high contribution of BCRP to their oral absorption. Furthermore, in vivo Rbcrp calculated in this study was almost comparable to in vitro AQ obtained from Caco‐2 permeability study. This study provides useful concepts in assessing the contribution of BCRP on intestinal absorption in drug discovery and development process.